IMPROVING VOCABULARY THROUGH IMPLEMENTING SONG AND GAME-BASED LEARNING STRATEGY OF ENGLISH FOR YOUNG LEARNERS - Iwan Fauzi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Although children learn a language faster than adults, they do not learn through traditional language teaching methods. Children can learn languages better through more fun activities so that language learning activities look natural to them as if they are not aware that they are learning a language. To attract the attention of young learners in learning a language, songs and games can be used as an effective learning strategy to teach young learners to speak English. This study shows the benefits of fun learning strategies of English to the young learners. There were 30 pupils of third graders at Muhammadiyah Primary School (SD- Muhammadiyah) Palangka Raya and one teacher of English at the school were modeled to this experimental study. This study using one group pretest-posttest design examined the effectiveness of implementation of song and game-based learning strategy of English vocabulary to Indonesian young learners. A comparison of learners’ proficiency in expressive and receptive vocabulary of English was made before and after the implementation of the learning strategy. Results indicated that the young learners’ proficiency in English vocabulary after implementing the strategy outperformed the learners’ proficiency before the strategy implemented.